Not erroneous but cautious conclusions about the potential effect of climate change on the geographical distribution of insect pest species in the Swedish boreal forest. Response to Björklund et al. (2015). Issue 1 (2nd January 2016) - Hof, Anouschka R.; Svahlin, Anna
ABSTRACT: We argue that the conclusions drawn from the paper "The potential effect of climate change on the geographical distribution of insect pest species in the Swedish boreal forest", published in the Scandinavian Journal of Forest Research were not erroneous as stated by a letter published in the same journal by Björklund et al. (2015. Erroneous conclusions about current geographical distribution and future expansion of forest insects in Northern Sweden: Comments on Hof and Svahlin (2015). Scand. J. Forest Res)", but cautious. We regret possible underestimations caused by lack of occurrence records for some species for some areas. However, basing predictions of the impact of future climate change on the distribution of species on current range maps likely leads to grave overestimations of future range predictions since current range maps assume species are homogenously distributed throughout the landscape, which is often not the case. We argue that underestimating the distribution range of pest species rather than overestimating their distribution pinpoints areas that may need extra attention in future better, and therefore chose to be cautious rather than bold. We further like to stress that one should always be aware of possible insect outbreaks throughout the region, not only because predictions may underestimate the future distribution of species but also since the location and likelihood of insect pest outbreaks is not only determined by climatic factors.